Barriers to adolescent female participation in cricket. Issue 4 (8th August 2021) - Fowlie, J.; Eime, R. M.; Griffiths, K.
ABSTRACT: With the ever-growing number of opportunities for females to participate in a range of sports without the previous associated gender norms, females are starting to become more involved in traditionally male-dominated sports, however, we know little about their barriers to participation. In this qualitative study, we investigated the barriers to adolescent female participation in cricket in a regional city in Victoria, Australia. The socio-ecological model was utilized to help guide semi-structured focus-group interviews with 20 adolescent females aged 10–12 years old. The participants identified the following as key barriers to their participation in cricket: lack of confidence in skills, having to play cricket with males, an absence of pathway opportunities, and no female only cricket competitions. These findings highlight the importance of adequate coaching specifically for females, female only teams and competitions, and the importance of developing a player pathway for adolescent girls.